Effects of erythropoietin on memory-relevant neurocircuitry activity and recall in mood disorders. - Miskowiak, K; Macoveanu, J; Vinberg, M; Assentoft, E; Randers, L; Harmer, C; Ehrenreich, H; Paulson, O; Knudsen, G; Siebner, H; Kessing, L (Wiley, 2016)
Objective Erythropoietin (EPO) improves verbal memory and reverses sub-field hippocampal volume loss across depression and bipolar disorder. This study aimed to investigate with functional magnetic resonance imaging (fMRI) whether these effects were accompanied by functional changes in memory-relevant neuro-circuits in this cohort. Method Eighty-four patients with treatment-resistant unipolar depression who were moderately depressed or bipolar disorder in remission were randomized to eight weekly erythropoietin (40,000 IU) or saline infusions in a double-blind, parallel-group design. Participants underwent whole-brain fMRI at 3T, mood ratings and blood tests at baseline and week 14. During fMRI, participants performed a picture encoding task followed by post-scan recall. Results Sixty-two patients had complete data (EPO: N=32, saline: N=30). EPO improved picture recall and increased encoding-related activity in dorsolateral prefrontal cortex (dlPFC) and temporo-parietal regions, but not in hippocampus. Recall correlated with activity in the identified dlPFC and temporo-parietal regions at baseline, and change in recall correlated with activity change in these regions from baseline to follow-up across the entire cohort. The effects of EPO were not correlated with change in mood, red blood cells, blood pressure or medication. Conclusion The findings highlight enhanced encoding-related dlPFC and temporo-parietal activity as key neuronal underpinnings of EPO-associated memory improvement.